Speech, communication and use of augmentative communication in young people with cerebral palsy: The SH&PE population study. Issue 2 (9th May 2013) - Cockerill, H.; Elbourne, D.; Allen, E.; Scrutton, D.; Will, E.; McNee, A.; Fairhurst, C.; Baird, G.
Abstract Background Communication is frequently impaired in young people (YP) with bilateral cerebral palsy (CP). Important factors include motoric speech problems (dysarthria) and intellectual disability. Augmentative and Alternative Communication (AAC) techniques are often employed. The aim was to describe the speech problems in bilateral CP, factors associated with speech problems, current AAC provision and use, and to explore the views of both the parent/carer and young person about communication. Methods A total population of children with bilateral CP (n = 346) from four consecutive years of births (1989–1992 inclusive) with onset of CP before 15 months were reassessed at age 16–18 years. Motor skills and speech were directly assessed and both parent/carer and the young person asked about communication and satisfaction with it. Results Sixty had died, eight had other conditions, 243 consented and speech was assessed in 224 of whom 141 (63%) had impaired speech. Fifty‐two (23% of total YP) were mainly intelligible to unfamiliar people, 22 (10%) were mostly unintelligible to unfamiliar people, 67 (30%) were mostly or wholly unintelligible even to familiar adults. However, 89% of parent/carers said that they could communicate 1:1 with their young person. Of the 128 YP who could independently complete the questions, 107 (83.6%) were happy with their communication, nine (7%) neither happy nor unhappy and 12 (9.4%) unhappy. A total of 72 of 224 (32%) were provided with one or more types of AAC but in a significant number (75% of 52 recorded) AAC was not used at home, only in school. Factors associated with speech impairment were severity of physical impairment, as measured by Gross Motor Function Scale level and manipulation in the best hand, intellectual disability and current epilepsy. Conclusions In a population representative group of YP, aged 16–18 years, with bilateral CP, 63% had impaired speech of varying severity, most had been provided with AAC but few used it at home for communication.